Propensity score matching comparing short-term nerve electrical stimulation to pulsed radiofrequency for herpes zoster-associated pain: A retrospective study - Liu, Liu; Zhang, Wen-jing; Xu, Shu-xiang; Guo, Wen-shuai; Yan, Ran-ran; Jiang, Xiao-han; Li, Shi-yao; Sun, Tao (Frontiers in Molecular Neuroscience, 2022)
Background: Zoster-associated pain (ZAP) is notoriously difficult to treat. Pulsed Radiofrequency (PRF) and short-term Nerve Electrical Stimulation (st-NES) have been proven effective treatments for ZAP. However, it is still unclear which technique provides improved analgesia in ZAP. This study is based on a large-scale, long-term follow-up to evaluate the efficacy and safety between st-NES and PRF. Methods: All eligible ZAP patients treated with st-NES or PRF in our department were enrolled. Cohorts were divided into the st-NES group and the PRF group. A 1:1 ratio propensity score matching (PSM) was used to balance the baseline characteristics. The PS-matched cohort was adopted to investigate the efficacy and safety of the two treatments. The ordinal regression analysis was performed to determine the variables affecting the treatment effect of ZAP. Results: 226 patients were included after PSM. The NRS scores in st-NES and PRF groups considerably reduced compared to baseline levels after treatment. The NRS scores in the st-NES group were obviously lower than those in the PRF group at discharge, 1, 3, 6, 12, and 24 months. During the follow-up period, the NRS reduction rate remained higher in the st-NES group than in the PRF group(P<0.01). The dosage of medication, PSQI score, and the number of patients with aggravated pain after discharge in the st-NES group were significantly less than in the PRF group after treatment. Conclusions: St-NES has been shown to be more advantageous than PRF for pain relief and quality of life improvement for ZAP patients.